Adição Nucleofílica de Sais de Potássio de Organotrifluoroboratos à Íons N-Acilimínio - Ferreira, Fernando da Paz [UNIFESP] (2009)
In this work, we developed a new methodology for the stereoselective acquisition of substituted pyrrolydin-2-ones in the 5 position through the addition of potassium organotrifluoroborate salts to cyclic N-acyliminium cations. The á-amidoalkylation reactions involve lactams derivative tartaric acid – (3R, 4R, 5R)-3,4-bis-(acetoxy)-5- hidroxy-1-benzyl-2-pyrrolydinone and alkyl, aryl, heteroaryl, allyl and alkynyl potassium organotrifluoroborate salts, providing substituted pyrrolydin-2-ones in the á position of 1 ab, with yield variable of 63% to 87% and diastereoselectivity of moderate to good, where the diastereoisomer syn were obtained preferentially in the cases where of the nucleophilic carbon have sp and sp2 hybridization and occurring the inversion of the diastereoselectivity, that is, preferentially the diastereoisomer anti in the case of carbon hybridization sp3. The relative stereochemistry syn/anti of the majority products were deduce through of the spectroscopic data of 1H and 13C NMR. The salts of heteroaryl, aryl, alkyl and acetylenes compounds were obtained through the generation of the respective organomagnesium and organolitium anions followed by the addition of trimethylborate at low temperature and further reaction with aqueous KHF2.